A simple and efficient enzymatic method for covalent attachment of DNA to cellulose. Application for hybridization-restriction analysis and for in vitro synthesis of DNA probes. - Goldkorn, T (1986)
Single-stranded DNAs (ssDNAs) were covalently bound by a simple and efficient enzymatic method to a solid support matrix and used to develop several new procedures for gene analysis. The novel procedure to prepare a ssDNA stably coupled to a solid support employed T4 DNA ligase to link covalently oligo (dT)-cellulose and (dA)-tailed DNA. Beginning with essentially any double stranded DNA the procedure generates a ssDNA linked by its 5' end to a cellulose matrix in a concentration of over 500 ng per mg. DNA from the plasmid pBR322 (4300 bp) and a fragment of the beta-globin gene (1800 bp) were coupled to the solid support and used for several experiments. The ssDNAs on the cellulose efficiently hybridized with as little as 5 pg of complementary double-stranded DNAs. The DNA hybrids formed on the solid support were specifically and efficiently cleaved by restriction endonucleases. These specific restriction cuts were utilized for the diagnosis of correct sequences. In addition, the ssDNA on the solid support served as an efficient template for the synthesis of complementary ssDNAs. The complementary synthesized ssDNAs were uniformly labeled, more than two kilobases in size, and largely full length. About 85% of the ssDNA linked to cellulose was available for the synthesis of complementary DNA, and after strand-separation, the preparation was reusable for the synthesis of additional complementary DNA.